Gestational or acute restraint in adulthood reduces levels of 5α-reduced testosterone metabolites in the hippocampus and produces behavioral inhibition of adult male rats - Walf, Alicia A.; Frye, Cheryl A. (Frontiers in Cellular Neuroscience, 2012)
Stressors, during early life or adulthood, can alter steroid-sensitive behaviors, such as exploration, anxiety, and/or cognitive processes. We investigated if exposure to acute stressors in adulthood may alter behavioral and neuroendocrine responses of male rats that were exposed to gestational stress or not. We hypothesized that rats exposed to gestational and acute stress may show behavioral inhibition, increased corticosterone, and altered androgen levels in the hippocampus. Subjects were adult, male offspring of rat dams that were restrained daily on gestational days 14-20, or did not experience this manipulation. Immediately before testing, rats were restraint-stressed for 20 minutes or not. During week 1, rats were tested in a battery of tasks, including the open field, elevated plus maze, social interaction, tailflick, pawlick, and defensive burying tasks. During week 2, rats were trained and tested 24 hours later in the inhibitory avoidance task. Plasma corticosterone and androgen levels, and hippocampal androgen levels, were measured in all subjects. Gestational and acute restraint stress increased plasma levels of corticosterone, and reduced levels of testosterone’s 5α-reduced metabolites, dihydrotestosterone and 3α-androstanediol, but not the aromatized metabolite, estradiol, in plasma or the hippocampus. Gestational and acute restraint stress reduced central entries made in the open field, and latencies to enter the shock-associated side of the inhibitory avoidance chamber during testing. Gestational stress reduced time spent interacting with a conspecific. These data suggest that gestational and acute restraint stress can have actions to produce behavioral inhibition coincident with increased corticosterone and decreased 5α-reduced androgens of adult male rats. Thus, gestational stress altered neural circuits involved in the neuroendocrine response to acute stress in early adulthood.